Electrochemical and AFM studies of the electrodeposition of cobalt on glassy carbon: an analysis of the effect of ultrasound - Floate, S; Hyde, M; Compton, R (2002)
The mechanism of cobalt electrodeposition cobalt on glassy carbon from an aqueous sulphate solution has been studied using electrochemical techniques such as cyclic voltammetry, linear stripping voltammetry (LSV) and chronoamperometry, as well as contact mode atomic force microscopy (AFM) which has allowed the complementary determination of morphological detail of the resulting deposits. The influence of power ultrasound (20 kHz) was then studied. At suitably high overpotentials cobalt electrocrystallisation under silent conditions proceeds via a diffusion controlled mechanism and was analysed using the Scharifker and Hills model for potentiostatic growth: at low overpotentials (ca. -1.0 V vs. SCE) growth occurred under charge transfer control. Nucleation was found to be more 'progressive' in character at -1.0 V vs. SCE while at elevated overpotentials (more negative than -1.25 V) an 'instantaneous' nucleation behaviour was determined. Sonication favoured 'instantaneous' deposition and generally increased the rate of cobalt deposition, although ablation was dominant at small electrode - tip/horn separations. AFM images confirmed these findings, showing cobalt clusters of varying sizes at low overpotential and silent conditions, and more uniformly sized clusters at higher overpotentials, particularly when sonication was applied. © 2002 Elsevier Science B.V. All rights reserved.